Offshoring Danish jobs to Germany: regional effects and challenges to workers' organisation in the slaughterhouse industry. (1st October 2012) - Bjarke Refslund
Abstract : Increasing internationalisation of production is often seen as causing an erosion of West European social systems and, in particular, the worker's position, but the macro-level empirical evidence is often flawed. This article provides evidence based on a case study of Danish slaughterhouses that offshoring strongly affects the power relations within the industry. These changes in industrial relations can largely be explained by developments in the German slaughterhouse industry and changes in European legislation which have greatly influenced a shift towards more precarious employment in slaughterhouses, using the work of subcontracted workers from Eastern Europe. This article analyses the significant role played by European integration and globalisation in altering the international division of labour and employer-employee relations.